Pandemic lockdowns: who feels coerced and why? - a study on perceived coercion, perceived pressures and procedural justice during the UK COVID-19 lockdowns - V. Ranieri; C. Gordon; S. K. Kamboj; S. J. Edwards (BMC, 2024)
Abstract Background This study examined perceptions of coercion, pressures and procedural injustice and how such perceptions influenced psychological well-being in those who experienced a UK COVID-19 lockdown, with a view to preparing for the possibility of future lockdowns. Methods 40 individuals categorised as perceiving the lockdown(s) as either highly or lowly coercive took part in one of six asynchronous virtual focus groups (AVFGs). Results Using thematic analysis, the following key themes were identified in participants' discussions: (1) Choice, control and freedom; (2) threats; (3) fairness; (4) circumstantial factors; and (5) psychological factors. Conclusions As the first qualitative study to investigate the psychological construct of perceived coercion in relation to COVID-19 lockdowns, its findings suggest that the extent to which individuals perceived pandemic-related lockdowns as coercive may have been linked to their acceptance of restrictions. Preparing for future pandemics should include consideration of perceptions of coercion and efforts to combat this, particularly in relation to differences in equity, in addition to clarity of public health messaging and public engagement.